2014
DOI: 10.5958/j.2230-732x.7.1.025
|View full text |Cite
|
Sign up to set email alerts
|

Bio-efficacy of chemical Insecticides against Spotted Pod Borer,Maruca testulalis(Geyer) on Cowpea

Abstract: Studies were conducted at Agricultural Research Farm, Banaras Hindu University, Varanasi during Kharif 2010 and 2011 to know the efficacy of some new molecule insecticides (azadirachtin, Bt, endosulfan 35% EC, thiodicarb 75% WP, spinosad 45% SC, lambda cyhalothrin 5% EC, indoxacarb 14.5% SC, profenophos 50% EC and acetamiprid 20% SP) against spotted pod borer, Maruca vitrata (Geyer) on mungbean. The spinosad 45% SC and indoxacarb 14.5 % SC were the most effective treatments and significantly superior to other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
3
2
0
Order By: Relevance
“…ha -1 (11.33, 7.44%). Similar reports were given by Yadav and Singh (2014) and Sonune et al (2010). Similarly, spinosad 45 SC was proved to be effective against Helicoverpa armigera Hubner and M. testulalis infesting greengram (Meena et al, 2022).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…ha -1 (11.33, 7.44%). Similar reports were given by Yadav and Singh (2014) and Sonune et al (2010). Similarly, spinosad 45 SC was proved to be effective against Helicoverpa armigera Hubner and M. testulalis infesting greengram (Meena et al, 2022).…”
Section: Resultssupporting
confidence: 88%
“…Similarly, an increase in grain yield (8.86 q/ ha) was obtained in spinosad treated green gram field by Singh and Singh (2019). The present findings are in agreement in Umbarkar and Parsana (2014), Yadav and Singh (2014), Kaushik et al (2016) and Meena et al (2022) who reported the maximum grain yield from spinosad treatment. Singh et al (2020) recorded the highest marketable yield in flubendiamide 20 WG @ 1.0 g/l (9.14 q/ ha) and spinosad 45 SC @ 0.3 ml/l (9.13 q/ ha).…”
Section: Effect Of Spinetoram 6% W/v + Methoxyfenozide 30% W/ V Sc On...supporting
confidence: 92%
“…This may be due to its broad-spectrum activity over pod borers and killing of larvae by causing rapid excitation with its unique mode of action. These results were in accordance with Yadav and Singh [10] who reported that the maximum yield in cowpea was recorded in treatment indoxacarb 14.5 SC (11.8 q ha -1 ) followed by spinosad 45 SC (11.1 q ha -1 ) which were at par with each other. The present findings are also in agreement with the reports of Mohapatra and Srivastava [11], Chandrayudu et al [12], Rani and Eswari [13], Kumar and Shivaraju [14] and Sonune et al [15].…”
Section: Effect Of Insecticidal Treatments On Yieldsupporting
confidence: 91%
“…The results were also in agreement with that of Rekha and Mallapur [7], Mallikarjuna et al [8] and Kulheri et al [9] who found spinosad as highly effective against pod borers. Yadav and Singh [10] reported that spinosad 45 SC and indoxacarb 14.5 SC were the most effective treatments and significantly superior to other treatments with 80.7 and 79.2 per cent larval reduction over control. Mohapatra and Srivastava [11], Chandrayudu et al [12], Rani and Eswari [13], Kumar and Shivaraju [14] and Sonune et al [15] have also reported the similar results.…”
Section: Effect Of Insecticidal Treatments On Per Cent Pod Damagementioning
confidence: 98%
“…Comprehensive analysis of two year's data from the experiment conducted during 2018-19 and 2019-20. The result of application of both seed treatment and foliar sprays with insecticides was found to be significantly elevated to the control ( The most common vector for MYMV is whitefly which was effectively managed by Imidacloprid, Spinosad (Yadav and Singh, 2014), and dimethoate (Yadav et al, 2015). For minimizing the whitefly population, scheduled spray of imidacloprid on 25 and 40 DAS was most effective found.…”
Section: Resultsmentioning
confidence: 99%